Analisis Risiko Proses Operasional Industri Tahu di Candisari, Kota Semarang - Jihan Zulfani; Azka Dwi Yuniar; Diandra Novitasari; Oktavinda Jihan Nurita; Evi Juliani Ayu Pratiwi; Amnan Haris; Andhina Putri Heriyanti (Jurnal Riptek, 2025)
The food industry has various potential risks that can affect workplace safety, production smoothness, and product quality. Loso Tofu Factory in Semarang City is a medium-scale industry facing such risks. This study aims to analyze risks in the tofu production process using the Failure Mode and Effect Analysis (FMEA) method and Risk Priority Number (RPN). Among 13 identified risks, five main risks were prioritized for mitigation: slippery production area (R10), soybean spillage due to employee slips caused by slippery areas (R9), tofu crumbling during cutting (R11), mixing of waste with soybeans (R2), and incorrect tofu cutting (R12). Mitigation measures include improving Standard Operating Procedures (SOP), conducting work training, using Personal Protective Equipment (PPE), and maintaining production equipment. The results demonstrate that implementing mitigation strategies can enhance workplace safety, production efficiency, product quality, and ensure industrial sustainability. This research underscores the importance of proactive risk management in maintaining operational continuity and product standards in the food industry. By addressing these prioritized risks, Loso Tofu Factory can minimize disruptions, reduce hazards, and strengthen its position as a sustainable medium-scale enterprise. The integration of FMEA and RPN provides a systematic approach to identifying and managing critical risks, offering a model for similar industries to improve safety and production outcomes.